PROBLEMS OF MANAGEMENT AND IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN PAI LESSONS IN PUBLIC ELEMENTARY SCHOOLS IN BESITANG DISTRICT, LANGKAT - Awan, Siti; Amini, Amini; Nurzannah, Nurzannah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this study is to examine the challenges management and associated with using the independent curriculum in PAI courses in state primary schools in Langkat, North Sumatra's Besitang District. The research focuses on the challenges teachers have when utilizing the autonomous curricular platform to teach and the obstacles they have while assessing PAI learning in their individual classrooms. Utilizing a multisite study method and a qualitative methodology, this research is conducted at SDN 050780 Besitang, SDN 050771 Halaban Blok, and SDN 056646 Sisirah Halaban. The study was conducted in January through March of 2024. Principals of the three state elementary schools as well as PAI teachers served as research informants. Methods such as observation, interviews, and documentation studies were used to gather data. According to the research's findings, teachers in the three elementary schools are having difficulty implementing the independent curriculum because of a lack of study space, poor learning resources and facilities in the school library, and shaky internet networks. Second, instructors' inability to be creative in their creation of digital learning materials and the surrounding environment, as well as their inability to integrate subjects into theme learning, is a challenge faced by them when implementing the autonomous curriculum. Third, challenges with assessing learning, such as modifying behavior (guiding the Pancasila student profile) and enhancing learning results for students.